[Craniocerebral trauma in childhood] - Struffert, T; Grunwald, I; Reith, W (2003)
This article describes typical head injuries in infants and children. In comparison with adults there are distinct differences in the etiology of trauma and in the kind of reaction of the skull and brain. In infants and children there are three different types of trauma: birth trauma, accidental and non-accidental injury. The typical injuries in these three groups are described.